Implementation of Child Identity Card Policy through Resources at the Population and Civil Registration Office of Mojokerto Regency - Rizqi Della Fransisca; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and describe the implementation of the child identity card policy as well as to analyze and describe the obstacles/barriers to the implementation of the child identity card policy at the Department of Population and Civil Registration of Mojokerto Regency. This study uses the theory of public policy implementation. The research method uses a qualitative descriptive approach using data collection techniques in the form of interviews, documentation, and observation. Data analysis techniques from Miles and Hurberman (2011: 247) are data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the policy on child identity cards at the Department of Population and Civil Registration of Mojokerto Regency can be viewed from the resource indicators, namely there are still some that have not been implemented. Minimal human resources, facilities in the form of printing machines and computers for identity cards are minimal, information related to children's identity cards is not maximized. Keywords: Policy Implementation, Population Administration, Child Identity Cards.